2012
DOI: 10.1186/1471-2164-13-139
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of nemertean complete mitochondrial genomes, including two new ones for Nectonemertes cf. mirabilis and Zygeupolia rubens, may elucidate the fundamental pattern for the phylum Nemertea

Abstract: BackgroundThe mitochondrial genome is important for studying genome evolution as well as reconstructing the phylogeny of organisms. Complete mitochondrial genome sequences have been reported for more than 2200 metazoans, mainly vertebrates and arthropods. To date, from a total of about 1275 described nemertean species, only three complete and two partial mitochondrial DNA sequences from nemerteans have been published. Here, we report the entire mitochondrial genomes for two more nemertean species: Nectonemerte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 79 publications
4
6
0
Order By: Relevance
“…Except for Tetrancistrum nebulosi (Young, 1967), the most abundant codon families were Leu2, Ile, and Phe. This is comparable to Lepidoptera [ 43 ] and Nemertea [ 44 ]. Noteworthy, the studied mt genome exhibited a strong preference for the A + T-rich members of these four codon families (>10%, Phe, Ile, Leu2 and Asn in Fig.…”
Section: Resultssupporting
confidence: 62%
“…Except for Tetrancistrum nebulosi (Young, 1967), the most abundant codon families were Leu2, Ile, and Phe. This is comparable to Lepidoptera [ 43 ] and Nemertea [ 44 ]. Noteworthy, the studied mt genome exhibited a strong preference for the A + T-rich members of these four codon families (>10%, Phe, Ile, Leu2 and Asn in Fig.…”
Section: Resultssupporting
confidence: 62%
“…In contrast, all represented taxa branching from the base of the annelid tree show a completely different arrangement of genes than observed in Pleistoannelida, but the reconstruction of a putative annelid mitochondrial ground pattern still remains difficult. However, as already mentioned, it seems very likely that all genes were encoded on one strand except for tRNA-P and tRNA-T, as found in the two annelids Owenia fusiformis and Magelona mirabilis and in the ground pattern of Nemertea(Chen et al, 2012;Chen et al, 2011). Additionally,…”
mentioning
confidence: 86%
“…The mitochondrial genes in brachiopods are generally encoded on one strand(Helfenbein et al, 2001) and in molluscs there is no general pattern. Different families of molluscs show a high diversity in strand usage and gene order(Osca et al, 2014).Interestingly, all but one mitochondrial genome of Nemertea, which are either sister group to Annelida or very closely related to them(Dunn et al, 2008; Laumer et al, 2015;Weigert et al, 2014), show a similar pattern to that found in Owenia fusiformis and Magelona mirabilis, where all genes are transcribed from one strand except for the two tRNAs encoding for threonine and proline (e.g (Chen et al, 2012;Chen et al, 2011)…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Nevertheless, several species are known to have important effects as active predators, especially on mollusks, crustaceans and annelids ( Roe 1976 ; Thiel and Kruse 2001 ; Caplins and Turbeville 2011 ). Nemerteans also have caught the attention of different biological fields such as regeneration ( Coe 1934 , 1943 ), developmental biology ( Martindale and Henry 1995 ; Maslakova et al 2004 ), genetics ( Andrade et al 2012 ; Chen et al 2012 ), and pharmacology ( Kem et al 2006 ).…”
Section: Introductionmentioning
confidence: 99%